Effect of two different surface treatments on implant stability - Loay Mohamed; Noha Nawar; Yasmine Thabet (Ain Shams University, Faculty of Dentistry, 2024)
Aim of the study: This study compered the effect of two different implant surface treatments (Direct laser metal forming and Acid etching) on implant stability in All-on-4 implant retained mandibular overdentures. Materials and methods: 14 male patients were selected to participate in this study. For each patient, four implants were inserted at the inter-foraminal region using the All-on-4 concept. Patients were randomly divided into two groups according to surface treatment of dental implants. Primary and secondary implant stability were measured and compared by resonance frequency analysis using the osstell device at the time of implant insertion, 3 months and 6 months after implant insertion.Results: Comparison was performed between the straight implants of both groups and revealed that implant stability of group I is significantly higher than group II after 3months and after 6 months, while revealed insignificant difference between them at the time of insertion. Comparison was performed between the angled implants of both groups and revealed that implant stability of group I is significantly higher than group II after 3months and after 6 months, while revealed insignificant difference between them in time of insertion.Conclusions: Direct Metal Laser Forming surface treatment increases the secondary stability of angled implants supporting All-On-4 temporary prosthesis.